PENGARUI.I VARIASI PENYUDUTAN ARAH SINAR PADA PEERIKSAAN VERTEBRA LUMBASACRAL JOINT PROYEKSI LATERAT TERHADAP KRITERIA ANATOMI RADIOGRAF - Utami, Asih Puji (STIKES Widya Husada Semarang, 2011)
There are variations in x-ray beam angulation applied in examining lumbosacral joint lateral projmtion, both heoretical and practical. According to Clark (1973) examination of lumbo